In the skin of a jihadist: a young journalist enters the ISIS recruitment network - Erelle, Anna (Harper Collins Publishers, 2015)
"A young French journalist's riveting and unprecedented look at how today's most ruthless terrorists use social media and technology to reach disaffected youth--witnessed through the undercover investigation that led to her deep involvement with a key member of ISIS, "--Novelist